2005
DOI: 10.1002/marc.200400647
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Vapor‐Induced Nanowire Formation in Poly(3‐hexylthiophene) Thin Films

Abstract: Summary: Nanowire lengths and length‐to‐width aspect ratios in regioregular poly(3‐hexylthiophene) (P3HT) were simply controlled through changes in the solvent vapor pressure during solidification. It is demonstrated that the nanowires grew by rod‐to‐rod association, in which the molecular long axis of the P3HT chains appeared to be well‐oriented parallel to the silicon substrate (Si/SiOx). The formation of the nanowires took place by one dimensional self‐assembly, governed by π‐π stacking of the P3HT units.TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 36 publications
7
113
0
Order By: Relevance
“…In the case of the pxylene sample (Figure 2(a)), a P3HT network composed of long fibers (with a typical width of 20-30 nm and a length of several micrometers) was observed in both the topography and phase signals. [18] After selectively removing the PEG phase by immersing the sample in acetone for 30 min, the P3HT network retained good connectivity (Figure 2(a 1 )). For the CH 2 Cl 2 sample, due to the strong aggregation tendency of P3HT molecules at room temperature, both nanofibrils and small aggregates were observed (Figure 2(b)).…”
Section: Crystallization-induced Vertical Stratified Structures Prepamentioning
confidence: 94%
“…In the case of the pxylene sample (Figure 2(a)), a P3HT network composed of long fibers (with a typical width of 20-30 nm and a length of several micrometers) was observed in both the topography and phase signals. [18] After selectively removing the PEG phase by immersing the sample in acetone for 30 min, the P3HT network retained good connectivity (Figure 2(a 1 )). For the CH 2 Cl 2 sample, due to the strong aggregation tendency of P3HT molecules at room temperature, both nanofibrils and small aggregates were observed (Figure 2(b)).…”
Section: Crystallization-induced Vertical Stratified Structures Prepamentioning
confidence: 94%
“…In general, a slow evaporation rate is favored for the formation and growth of crystals in films. Kim et al reported that the gradual growth of aggregates of P3HT from few nucleates to a large amount of long nanowires during spin-coating via reducing evaporation rate of chloroform tuned by a larger vapor pressure of chloroform in atmosphere (Figure 23a) [165]. Chang et al realized the formation of P3HT nano-ribbon with a diameter of 30-50 nm in film by using a good solvent with a extremely high boiling point (219 °C), 1,2,4-trichlorobenzene, to largely reduce the evaporation rate of solvent (Figure 23b) [166].…”
Section: Promotion Of Coil-to-rod Transition and Ordered Rod-rod Stacmentioning
confidence: 99%
“…In the realm of semiconductive polymers, large single rectangular crystals of 3-hexyl thiophene (3HT) 8 [35,36], nanowires of conjugated poly(p-phenylene ethynylene) derivatives [37], poly(3-hexyl thiophene) (P3HT) nanowhiskers [38], one-dimensional (1D) microwire P3HT single crystals [39], and self-organized two-dimensional (2D) P3HT supramolecules [40,41] were reported. Nascent lateral habits of solution-grown single crystals [42], surface-patterned single crystals [43][44][45][46][47], and conductive-dielectric-conductive single crystals [48][49][50] have also been reported.…”
Section: Introductionmentioning
confidence: 99%